Asymmetric Information and Non-Performing Financing: Study in The Indonesian Islamic Banking Industry - Rodoni, Ahmad; Yaman, Bahrul (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
The purposes of this study are: First, to analyze the indications of moral hazard and adverse selection on Indonesian Islamic commercial banks. Second, to analyze the influence of moral hazard and adverse selection on the Non Performance Financing of Indonesian Islamic banks. Two methods were used for this purpose, a qualitative content analysis approach derived from the results of interviews with the banker from the Islamic commercial banks. Besides that this study also uses Error Correction Model (ECM), with data taken from these listed Islamic banking from 2010 to June 2016. The results show that the indications of moral hazard have a positive effect on the non-performing financing (NPF) in the short run. The indication of the presence of moral hazard occurs at the long run on GDP variable, and the allocation of Murabaha financing (RM) has a positive effect on the mudharabah (FM) profit and loss sharing. The test results also show that adverse selection that represented by the profit sharing rate (PSR) has a positive effect on the level of risk sharing toward non-performing financing (NPF) in the long run.DOI: 10.15408/aiq.v10i2.7392